Does kinematic alignment increase polyethylene wear compared with mechanically aligned components?: A wear simulation study - Schröder, Stefan; Schonhoff, Mareike; Uhler, Maximilian; Braun, Steffen; Jäger, Sebastian; Renkawitz, Tobias; Kretzer, Jan Philippe (Clinical orthopaedics and related research, 2022)
Background Kinematic alignment is an alternative approach to mechanical alignment. Kinematic alignment can restore the joint line to its prearthritic condition, and its advocates have suggested it may be associated with other benefits. But this alignment approach often results in tibial components that are placed in varus and femoral components that are placed in valgus alignment, which may result in an increased risk of component loosening because of wear. Like malaligned implant components, kinematically aligned knee implants could increase wear in vivo, but we lack comparative data about wear behavior between these approaches. Questions/purposes (1) Do the different alignment approaches (kinematic, mechanical, and purposefully malaligned components) result in different wear rates in a wear simulator? (2) Do the different alignment approaches lead to different worn areas on the polyethylene inserts in a wear simulator? (3) Do the different alignment approaches result in different joint kinematics in a wear simulator? Methods Mechanical alignment was simulated in a force-controlled manner with a virtual ligament structure according to the International Organization for Standardization (ISO 14243-1) using a knee wear simulator. To simulate kinematic alignment, flexion-extension motion, internal-external torque, and the joint line were tilted by 4 degrees, using a novel mechanical setup, without changing the force axis. The setup includes bearings with inclinations of 4 degrees so that the joint axis of 4 degrees is determined. To verify the angle of 4 degrees, a digital spirit level was used. To simulate malalignment, we tilted the implant and, therefore, the joint axis by 4 degrees using a wedge with an angle of 4 degrees without tilting the torque axes of the simulator. This leads to a purposefully malaligned tibial varus and femoral valgus of 4 degrees. For each condition, three cruciate-retaining knee implants were tested for 3.0 x 10(6) cycles, and one additional implant was used as soak control. Gravimetric wear analyses were performed every 0.5 x 10(6) cycles to determine the linear wear rate of each group by linear regression. The wear area was measured after 3.0 x 10(6) cycles by outlining the worn areas on the polyethylene inserts, then photographing the inserts and determining the worn areas using imaging software. The joint kinematics (AP translation and internal-external rotation) were recorded by the knee simulator software and analyzed during each of the six simulation intervals. Results Comparing the wear rates of the different groups, no difference could be found between the mechanical alignment and the kinematic alignment (3.8 +/- 0.5 mg/million cycles versus 4.1 +/- 0.2 mg/million cycles; p > 0.99). However, there was a lower wear rate in the malaligned group (2.7 +/- 0.2 mg/million cycles) than in the other two groups (p < 0.01). When comparing the total wear areas of the polyethylene inserts among the three different alignment groups, the lowest worn area could be found for the malaligned group (716 +/- 19 mm(2); p <= 0.003), but there was no difference between kinematic alignment and mechanical alignment (823 +/- 19 mm(2) versus 825 +/- 26 mm(2); p > 0.99). Comparing the AP translation, no difference was found between the mechanical alignment, the kinematic alignment, and the malalignment group (6.6 +/- 0.1 mm versus 6.9 +/- 0.2 mm versus 6.8 +/- 0.3 mm; p = 0.06). In addition, the internal-external rotation between mechanical alignment, kinematic alignment, and malalignment also revealed no difference (9.9 degrees +/- 0.4 degrees versus 10.2 degrees +/- 0.1 degrees versus 10.1 degrees +/- 0.6 degrees; p = 0.44). Conclusion In the current wear simulation study, the wear rates of mechanical alignment and kinematic alignment of 4 degrees were in a comparable range.
Gesehen am 28.09.2022